2021
DOI: 10.1186/s12940-021-00744-9
|View full text |Cite
|
Sign up to set email alerts
|

Ambient PM gross β-activity and glucose levels during pregnancy

Abstract: Background Exposure to ionizing radiation has been associated with insulin resistance and type 2 diabetes. In light of recent work showing an association between ambient particulate matter (PM) gross β-activity and gestational diabetes mellitus (GDM) among pregnant women, we examined pregnancy glucose levels in relation to PM gross β-activity to better understand this pathway. Methods Our study included 103 participants receiving prenatal care at B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…This paper was among the first studies to investigate exposures to phthalate mixtures as they relate to glycaemic outcomes in pregnancy. In a separate study, our team found an association between exposure to higher levels of ambient particulate matter (PM) gross beta-activity, a measure of exposure to environmental radiation via inhalation of radioactive PM components, and higher blood glucose levels during pregnancy within a subset of ERGO participants 116…”
Section: Findings To Datementioning
confidence: 99%
See 1 more Smart Citation
“…This paper was among the first studies to investigate exposures to phthalate mixtures as they relate to glycaemic outcomes in pregnancy. In a separate study, our team found an association between exposure to higher levels of ambient particulate matter (PM) gross beta-activity, a measure of exposure to environmental radiation via inhalation of radioactive PM components, and higher blood glucose levels during pregnancy within a subset of ERGO participants 116…”
Section: Findings To Datementioning
confidence: 99%
“…In a separate study, our team found an association between exposure to higher levels of ambient particulate matter (PM) gross beta-activity, a measure of exposure to environmental radiation via inhalation of radioactive PM components, and higher blood glucose levels during pregnancy within a subset of ERGO participants. 116 A pilot project supported by the MOD Foundation (research grant #6-FY19-367) leveraged laboratory data and ERGO participant data to investigate personal care product use as it relates to EDC exposure and health pregnancy in a series of recent publications. [117][118][119][120] reporter gene assays, we found evidence of hormonal activity among commonly used hair products, including hair oils.…”
Section: Findings To Datementioning
confidence: 99%
“…In addition to traditional risk factors, new data suggest that environmental and psychosocial factors are also risk factors for the development of GDM 7,8 . GDM may be harmful to both mother and fetus, for example, by increasing the risk of maternal pre‐eclampsia 9 and of macrosomia 10 in the fetus. Therefore, it is most important to screen for potential diagnostic biomarkers of GDM and to promote the study of the pathologic mechanisms of GDM.…”
Section: Introductionmentioning
confidence: 99%